STUDI KEANEKARAGAMAN JENIS BURUNG DIURNAL DI HUTAN MANGROVE PANTAI AIR MATA PERMAI KABUPATEN KETAPANG Study of The Diurnal Bird Species Diversity in Mangrove Forests Pantai Air Mata Permai Ketapang District - Syahadat, Faqih; anto, Eri; Siahaan, Sarma (Universitas Tanjungpura, 2015)
ABSTRACT Tear Coast region Permai Ketapang Regency is one of the important areas for the presence of birds, especially birds protected. The purpose of this study was to determine the diversity of bird species and determine the abundance of each species of birds Mangrove Forest region of Tears Permai Village Beach Cloud River right Ketapang. The research was conducted in the mangrove forest along the beach Tears Permai Ketapang about 3 weeks time research done from March 5 to March 25, 2014. The method used in this research is the method of lines, amounting to 5 with the observations one lane per day. Bird species found as many as 61 species with Family 27 and 10 of the Order with the overall individual numbered 916. Diurnal bird community in this region is dominated types Beach Sandpipers (Tringa hypoleucos) and Long-tailed Parrots (Psittavula alexandri). Dominance index value is highest type in the morning and afternoon that the value of C in the morning = 1.2829, C = 1.529 afternoon with the index range D = 1 which means relatively stable. Index of species diversity is highest in the morning with a value of H 'morning = 3.2210 with a range of index H> 3 which means it has a high species diversity. Indeks kemerataan jenis tertinggi terdapat pada waktu pagi dan siang dengan nilai E pagi = 1,8041, E siang = 1,6320 dengan kriteria indeks kemerataan yaitu >1 yang berarti pada waktu pagi dan siang kemerataan jenisnya merata. Keywords: Diversity, type birds diurnal, mangrove forests.